Plasma Cell Myeloma in Children and Young Adults: A Report of 4 Cases From a Single Institution and a Review of the Literature. Issue 6 (August 2017) - Yohe, Sophia; Luquette, Mark; Lund, Troy C.; Turcotte, Lucie M.; Dolan, Michelle; McKenna, Robert W.
Abstract : Plasma cell myeloma (PCM) is rare in children and young adults and therefore may be difficult to diagnose. Here we report the clinicopathologic findings of 4 patients under the age of 30 diagnosed with PCM at our institution and summarize the literature about 48 other cases of PCM in this age group. The male:female ratio was 1.2:1 and the number of cases increased with age. Children and young adults with PCM often present with a plasmacytoma and are less likely to have asymptomatic PCM than their adult counterparts. From the cases that reported ethnicity, the majority (55%) were non-white suggesting a possible ethnic predisposition to PCM in this age group. PCM should be included in the differential diagnosis of mass lesions, especially a destructive bony lesion, after more common causes have been ruled out in this age group. The optimal treatment for PCM in this patient population is unclear and conclusions into this are hampered by the paucity of cases and the lack of standardized follow-up. Abstract : Supplemental Digital Content is available in the text.